Slovak Virtual Market in the Light of Analysis af Possibilities of Detecting On-Line Reputation for Selected Subjects - Dorcak, Peter; Pollak, Frantisek; Mudrik, Martin; Nastisin, Ludovit (Communications - Scientific Letters of the University of Zilina, 2014)
The main aim of this article is to analyze the theoretical possibilities of detecting an On-Line reputation of selected subjects functioning on Slovak virtual market. The purpose of article is also to present selected method of measuring on-line reputation of selected subjects based on newest knowledge in the field of managerial sciences. For purposes of this article, subjects are represented by on-line presence of Slovak towns in a virtual market place. In particular, cultural and anthropological context, and the resulting specificities and peculiarities typical of the post-communist block of countries will be taken into account in relation to the chosen market. The target group is narrowed to 20 biggest Slovak towns as the best representation of subjects which officially presented themselves to internet users on the specific type of market.
Keywords: reputation; on-line reputation; SME; market; entrepreneurship; competition; image; internet; social networks; virtual social networks